PENDIDIKAN NILAI KARAKTER SISWA DALAM KEGIATAN EKSTRAKURIKULER DI PONDOK PESANTREN TAHFIDHUL QUR’AN AL IKHLAS SUKOHARJO - SRI DADI; Oong Oong (PASCASARJANA UNISNU, 2021)
AbstractEducation in Indonesia has not been fully matured in instilling the tradition of character education as a performance in culture and religiuity in public life. This research aims to describe the value of student character in extracurricular activities in pesantren al ikhlas. Research in the form of qualitative descriptive with social psychology approach. The location of the research in pesantren Tahfidhul qur'an al ikhlas scratch Demakan Mojolaban Sukoharjo. The research was conducted in March 2021. The trainers, principals, waka madrasah students, karate and scouts became the primary data sources and subjects in this study. Secondary data sources in this study in the form of research results, scientific works, guidebooks, articles and others that can support. Data collection techniques using interview, observation and documentation techniques. Data analysis techniques use interactive models that take place in overlapping circles. The results of the study found a pattern of education in Pondok Pesantren Al Ikhlas. The values of character found in extracurricular activities are discipline, confidence, religion, responsibility, and sportsmanship. Then the values of character in scouting activities include being responsible, trustworthy, willing to help, steadfast, diligent, skilled, happy, disciplined, courageous and loyal.Keyword: Character Education, Extracurricular, Pesantren Al Ikhlas.